THE IMPACT OF SOCIAL INTERACTIONS ON THE STREETS ON URBAN MENTAL HEALTH OF UNIVERSITY STUDENTS IN BANDUNG, INDONESIA - Arifatul Hasanah; Imas Nurrahmah Priandani; Hanson Endra Kusuma (Tata Kota dan Daerah, 2025)
Urbanization is associated with increased psychological problems among urban dwellers, including university students. Streets, as public social spaces, can play a crucial role in reducing loneliness and improving mental health and resilience. Convivial street interactions, such as meeting strangers, can build social capital, increase community engagement, and enhance social well-being. This research aims to explore university students' perspectives on the streets they frequent daily and the impact of these streets on their mental health. Employing a mixed-methods approach, an online questionnaire with both open- and close-ended questions was distributed to 100 university students in Bandung. Results indicate that 79% of respondents perceive street interactions as positive as enhancing their mood, while 21% view them negatively. Despite this, interactions with strangers on the streets are infrequent. The study finds a significant correlation between street interactions and mental health, with 73% of respondents reporting moderate to high-stress levels linked to low interaction frequency, particularly with vendors/sellers. The poor physical conditions of streets and their primary role as vehicular passageways discourage on-street interactions. The findings underscore the importance of designing streets as "bumping places" and third places with human-centric designs to improve the mental health of university students in Bandung.